Detailed Analysis of Rare Causes of Secondary Duodenitis in Patients Diagnosed with Endoscopic Duodenitis: A Cross-Sectional Study from a Tertiary Referral Center - Atilla Bulur; Uguray Payam Hacisalihoglu (Haseki Tıp Bülteni, 2021)

(untitled)
Aim:Findings compatible with duodenitis are not rare in patients who have undergone endoscopy. Although the final histopathological diagnoses in most of these cases are chronic primary non-specific duodenitis, less commonly, there are also diseases that cause secondary duodenitis, too. We aimed to examine the causes of secondary duodenitis in our patients in detail.Methods:Upper gastrointestinal endoscopic procedures of 3.776 adult patients performed for various reasons in our endoscopy unit (Istanbul Yeni Yuzyıl University, Medical Faculty, Gaziosmanpasa Hospital, Department of Gastroenterology) between 2017 and 2021 were reviewed retrospectively by scanning the hospital automation system. The demographic, clinical, endoscopic, and histopathological features of the patients who underwent endoscopic biopsies with a prediagnosis of duodenitis were examined.Results:Biopsies with a pre-diagnosis of duodenitis were performed on 231 (6.12%) of 3776 adult patients during the endoscopic procedures. The mean age of the patients was 42.03 years (18-89 years); 42.4% were males and 57.6% were female. The most common symptoms/signs of the patients were dyspepsia (45%), chronic diarrhea (38%), and iron deficiency anemia (34%), respectively. The two main histological diagnoses were primary non-specific duodenitis (58.44%) and celiac disease (29.87%). In the remaining cases, various causes of secondary duodenitis such as graft versus host disease, eosinophilic duodenitis, Brunner’s gland adenoma, polyps, giardiasis, Crohn’s disease, cytomegalovirus duodenitis, and amyloidosis were detected.Conclusion:Although the most common etiology of duodenitis we encountered in our study was primary non-specific duodenitis, a considerable number, and variety of other etiologies of secondary duodenitis were also detected. Among many causes of secondary duodenitis, celiac disease should be kept in mind especially in female patients with younger age, presenting with dyspepsia.